Dewatering effect on dredged slurry clay by different types of drainage materials - S O Flemmy; K Omine; Z Zhang (Lowland Technology International, 2020)
Kumamoto slurry clay has high water content and organiccontent. From the preliminary test, it was found thatimprovement effect of this clay by adding hardening agent suchas cement is very small. It was also suggested that dewateringof the clay is important for improvement. In this work, severaltypes of drainage materials were installed in the slurry clay inthe field and laboratory test conditions, respectively. A simpledewatering method of soft clay using geotextile as drainagematerials was proposed based on the dewatering test results.The effect of the drainage materials on the slurry clay wereevaluated by ratio of 7 day water content and initial watercontent of the slurry clay (w7/w0). The ratio of w7/w0 in thesamples with string and cloth was 0.55 under the effectivedrainage condition in the laboratory test. The values of w7/w0 onthe field dewatering tests with the drainage materials (string andcloth) are below 0.75. In the laboratory and field dewateringtests, 25 and 35 kPa vacuum pressure can be obtained,respectively. It is indicated that the drainage materials areeffective for reducing the water content of the slurry clay withoutapplying external force of energy.